An Empirical Analysis of User’s Continuance Intention (UCI) towards Careem Mobile Application - Gharaibeh, Malik Khlaif; Gharaibeh, Natheer Khlaif (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This study aims at constructing a theoretical model to discover the main drivers on the user’s continuance intention (UCI) to use the Careem application in Jordan. This study also focuses on exploring new factors appropriate to the Jordanian environment that can shape people’s behavior towards adopting this smart service. Partial least square was performed to test the research model using 500 valid surveys. All constructs in this study were significant and accounted for 47.1% of the variance of continuance intention to use the Careem application. Careem user experience, E-word of mouth, financial benefits, and perceived platform quality are found strongest predictors toward intention to use at level (0.001). Two predictors were at level (0.01) including perceived enjoyment and perceived innovativeness. The findings also indicate that family confidence and women empowerment are the weakest effects at level (0.05). This article provides important information for future researchers in the field of technology acceptance, and more specifically in the field of mobile phone applications in terms of adding new variables that contribute to understanding users’ intention to continue using technology. Some of the implications this study provides for designers and developers of mobile applications and institutions related to transport when providing mobile application services.